The Effect of Supply Chain Dynamism and Supply Chain Disruption Orientation on Supply Chain Resilience in Indonesian Manufacturing Industry - M. Jihadi; Indrianawati Usman; Asrini Asrini; Musnaini Musnaini; Lutfi Lutfi; Sigit Indrawijaya; Dahmiri Dahmiri (International Journal of Supply Chain Management, 2020)
Supply chains are starting to be more and more powerful in reaction to transforming company atmosphere as well as innovation. This has produced issues in coping with the flow of resources as well as produced increased probability of interruption. As such this particular analysis evaluates the effect of dynamism on interruption orientations, financial performance, and resilience. Whereas, an incorporated theoretical model is designed and afterwards analyzed utilizing survey information from a cross section of 345 workers from Indonesian manufacturing industry and partial least squares - structural equation modelling (PLS-SEM). The outcomes belonging to the research show that supply chain dynamism possesses a substantial favorable impact on supply chain disruption orientation and also supply chain resilience. Supply chain resilience also is afflicted with supply chain disruption orientation.